Prospects of bioinformatics approach for exploring and mapping potential bioactive peptide of Rusip (The traditional Indonesian fermented anchovy): A Review - Muhammad Alfid Kurnianto; Fathma Syahbanu; Hamidatun Hamidatun; Ifwarisan Defri; Yushinta Aristya Sanjaya (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Rusip is a traditional Indonesian side-dishes food that is a fermented anchovy product originating from Bangka Belitung. During the fermentation, various lactic acid bacteria grew in rusip and produced bioactive peptides because of proteolytic enzyme action. Several treatments to obtain bioactive peptides can be conducted (fermentation, in vivo digestion, and in vitro hydrolysis using enzymes). The in vivo and in vitro methods are a widely used approach, but these methods are costly and time-consuming. These limitations could be solved by the bioinformatics approach. This method manages and interprets information about biological systems that employ computational methods. This study aimed to review recent studies on rusip and similar fermented fish and peptide bioactive with their bioactivity), steps, advantages, and limitations of bioactive peptide studies using the bioinformatics approach. The review article was written using narrative literature review method, which based on in-depth investigation from scientific literatures by identifing keywords, reviewing the content of articles, and synthesizing the findings. The results showed that using bioinformatics has provided opportunities for the development of bioactive peptides. Through this method, bioactive peptide identification begins with determining the main sample protein and the enzymes in protein hydrolysis. The further steps are protein hydrolysis simulation, determining the potential for bioactivity, and molecular docking. The bioinformatics analyses were performed synergistically to predict the protein or peptide characteristics from the sample and its bioactivity and determine its interaction with their receptor. However, despite the advantages, the bioinformatics approach also has several limitations, such as the lack of certain types of proteins or peptides in the database and hydrolysis simulation tool. Combining conventional and in silico methods (hybrid method) is potential to obtain the new and promising bioactive peptides from rusip and other fermented fish (i.e., budu, bekasam, and pla duk ra) and meat products for development product, both functional food and supplements.